5′-Morpholino modification of the sense strand of an siRNA makes it a more effective passenger. Issue 35 (12th April 2019) - Kumar, Pawan; Parmar, Rubina G.; Brown, Christopher R.; Willoughby, Jennifer L. S.; Foster, Donald J.; Babu, I. Ramesh; Schofield, Sally; Jadhav, Vasant; Charisse, Klaus; Nair, Jayaprakash K.; Rajeev, Kallanthottathil G.; Maier, Martin A.; et al.
Abstract : Blocking 5′-phosphorylation of the sense strand favours selective loading of the antisense strand into RISC complex. Abstract : The 5′-monophosphate group plays an important role in strand selection during gene silencing mediated by small-interfering RNA. We show that blocking of 5′ phosphorylation of the sense strand by introducing a 5′-morpholino modification improves antisense strand selection and RNAi activity. The 5′-morpholino modification of the antisense strand triggers complete loss of activity.